Deep inside a neoproterozoic intra-oceanic arc: growth, differentiation and exhumation of the Amalaoulaou complex (Gourma, Mali) - (:unkn) unknown (My University, 2011)
We show here that the Amalaoulaou complex, in the Pan-African belt of West Africa (Gourma, Mali), corresponds to the lower and middle sections of a Neoproterozoic intra-oceanic arc. This complex records a 90-130-Ma-long evolution of magmatic inputs and differentiation above a subducting oceanic slab. Early c. 793 Ma-old metagabbros crystallised at lower crustal or uppermost mantle depths (25-30 km) and have geochemical characteristic of high-alumina basalts extracted from a depleted mantle source slightly enriched by slab-derived sedimentary components ((La/Sm)(N) < 1; epsilon(Nd): +5.4-6.2; Sr-87/Sr-86: 0.7027-0.7029). In response to crustal thickening, these mafic rocks were recrystallised into garnet-granulites (850-1,000A degrees C; 10-12 kbar) and subject to local dehydration-melting reactions, forming trondhjemititic leucosomes with garnet-clinopyroxene-rutile residues. Slightly after the granulitic event, the arc root was subject to strong HT shearing during partial exhumation (detachment faults/rifting or thrusting), coeval with the emplacement of spinel- and garnet-pyroxenite dykes crystallised from a high-Mg andesitic parental magma. Quartz and hornblende-gabbros (700-660 Ma) with composition typical of hydrous volcanic rocks from mature arcs ((La/Sm)(N): 0.9-1.8; epsilon(Nd): +4.6 to +5.2; Sr-87/Sr-86: 0.7028-0.7031) were subsequently emplaced at mid-arc crust levels (similar to 15 km). Trace element and isotopic data indicate that magmas tapped a depleted mantle source significantly more enriched in oceanic sedimentary components (0.2%). Exhumation occurred either in two stages (700-660 and 623 Ma) or in one stage (623 Ma) with a final exhumation of the arc root along cold P-T path (550A degrees C, 6-9 kbar; epidote-amphibolite and greenschist facies conditions) during the main Pan-African collision event (620-580 Ma). The composition of magmas forming the Cryogenian Amalaoulaou arc and the processes leading to intra-arc differentiat
Keywords: African Research